Prediction of changes in visual acuity and contrast sensitivity function by tissue redness after pterygium surgery - Hilmi, Mohd Radzi; Che Azemin, Mohd Zulfaezal; Mohd. Kamal, Khairidzan; Mohd Tamrin, Mohd Izzuddin; Abdul Gaffur, Norfazrina; Tengku Sembok, Tengku Mohd (Taylor & Francis, 2017)
The goal of this study was to predict visual acuity (VA) and contrast sensitivity function (CSF)with tissue redness grading after pterygium surgery. A total of 67 primary pterygium participants were selected from patients who visited an ophthalmology clinic. We developed a semi-automated computer program to measure the pterygium fibrovascular redness from digital pterygium images. The final outcome of this software is a continuous scale grading of 1 (minimum redness) to 3 (maximum redness). The region of interest (ROI)was selected manually using the software. Reliability was determined by repeat grading of all 67 images, and its association with CSF and VA was examined. The mean and standard deviation of redness of the pterygium fibrovascular images was 1.88 ± 0.55. Intra-grader and inter-grader reliability estimates were high with intraclass correlation ranging from 0.97 to 0.98. The new grading was positively associated with CSF (p < 0.01) and VA (p < 0.01). The redness grading was able to predict 25% and 23% of the variance in the CSF and the VA, respectively. The new grading of pterygium fibrovascular redness can be reliably measured from digital images and showed a good correlation with CSF and VA. The redness grading can be used in addition to the existing pterygium grading.